2013
DOI: 10.2478/v10200-012-0030-y
|View full text |Cite
|
Sign up to set email alerts
|

American cockroach control assays in the municipal sewerage system of Valencia (Spain)

Abstract: Several insecticides (including different active substances and formulations) were applied to sewer shafts to control Periplaneta americana (LINNAEUS, 1758) populations in Valencia (eastern Spain). Results show that the best products for cockroach control were the paints (with and without insecticide), which provided an optimal reduction of P. americana populations for up to three months (P < 0.001). Therefore, it is important to note that the reduction of cockroach populations as well as the persistence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In this regard, a recent study focused on evaluating fear and disgust reactions of common animals showed that cockroaches are perceived as more disgusting than grass snakes while evoking similar levels of fear (Polák et al, 2020 ). The common presence of cockroaches in the cities of tropical and humid areas, as the Mediterranean zones (Bueno-Marí et al, 2013 ) where the prevalence of this disorder is especially high, aggravate this problem. Hence, we believe that our findings can contribute to this research field, helping and encouraging future studies to compare different specific phobia subtypes, delving and further describing its cognitive and neural processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, a recent study focused on evaluating fear and disgust reactions of common animals showed that cockroaches are perceived as more disgusting than grass snakes while evoking similar levels of fear (Polák et al, 2020 ). The common presence of cockroaches in the cities of tropical and humid areas, as the Mediterranean zones (Bueno-Marí et al, 2013 ) where the prevalence of this disorder is especially high, aggravate this problem. Hence, we believe that our findings can contribute to this research field, helping and encouraging future studies to compare different specific phobia subtypes, delving and further describing its cognitive and neural processes.…”
Section: Discussionmentioning
confidence: 99%
“…Cockroach phobia is a highly prevalent disorder in several parts of the world, especially in cities where these animals are common, such as Mediterranean zones (Bueno-Marí et al, 2013 ). We believe that cockroach phobia could be relevant in the phobic research field due to the lack of knowledge about the cognitive and behavioral mechanisms involved in its etiology and maintenance, in comparison with other widely studied animal phobias (Öhman, 1993 ; Öhman & Mineka, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 3 ) Baits of 5% carbaryl and 50% boric acid. All the insecticides were prepared according to the description ( 17 ). All of applied pesticides in this study were purchased from Bayer Company (Bayer Persian AG), Tehran, Iran.…”
Section: Methodsmentioning
confidence: 99%
“…Insecticide formulations of baits, dusts, and sprays have been applied for control of the American cockroaches. In this regard few studies are available about the formulation efficacy of insecticides for control of the American cockroaches in sewers 20,21,23,24 . Therefore, a study designs to evaluate the efficacy of insecticide formulations against the American cockroaches in sewer of Esfahan.…”
Section: Introductionmentioning
confidence: 99%